Fuelling an investigative mindset: the importance of pre-interview planning in police interviews with suspects - Chin, Jeffery (Psychology, crime & law, 2024)
Pre-interview planning is vital in interviews with suspects. Via a questionnaire administered to 596 police investigators in Singapore, the current study examined potential associations between pre-interview planning, interviewing behaviours and interview outcomes. Interviewing behaviours were hypothesised to mediate the relationship between pre-interview planning and interview outcomes. It is posited that pre-interview planning fosters an investigative mindset, which in turn, influences the nature of interviewing behaviours employed by investigators. The study also sought to provide insights into police interviews with suspects in Singapore, given the limited research from Singapore on the topic. Rapport-based interviewing behaviours were found to mediate the relationship between pre-interview planning and positive interview outcomes, contributing empirical support to the importance of pre-interview planning. In addition, accusatorial interviewing behaviours were associated with negative interview outcomes. This study also found that police investigators in Singapore reported frequent planning prior to their interviews and used rapport-based interviewing behaviours with suspects. These behaviours are in line with the interviewing model adopted in Singapore. Regression analyses showed that participants’ endorsement of rapport-based approaches was predicted by investigator experience, confidence, and interview length. Endorsement of pre-planning of interviews was also predicted by investigator confidence and interview length. Implications of these findings are discussed.